Pelaksanaan Discharge Planning oleh Profesional Pemberi Asuhan (PPA) di Ruang Rawat Inap - Richa Noprianty; Sri Noviyanti (Jurnal Kesehatan Vokasional, 2019)
Background: Discharge planning in hospital still not optimal on its implementation, so it could affect quality of hospital service and result in rehospitalization patient, especially for hospital with high relapse number. Discharge planning is an integrated manner involving professional caregiver such as doctor, nurse, nutritionist, clinic pharmacy, and physiotherapy.Objective: This research aims to identify implementation of discharge planning by professional caregiver.Methods: This research type descriptive observasional with survey approach. Research Population 208, with proportionate stratified random dsampling data collection method that starts from 07.00 WIB until 17.00 WIB. With 68 implementation of discharge planning patient admission until to go home with minimum care for 2 days. Instrument use format of discharge planning assessment which modified with integrated education format.Results: The results showed that implementation of physician 67,6% implemented, 77,9% of nurses implemented, 94,1% of nutritionists implemented, 67,6% of clinical pharmacy implemented, and 58,8% physiotherapyimplemented. For the most not action is about the usage of tools for home care needs in physiotherapy items with percentage of 100%.Conclusion: Implementation of discharge planning by Professional Caregiver on Inpatient Room showed 60.3% implemented. Therefore it is necessary to monitoring and government of nursing managers for implementation of discharge planning can be implemented with good and improve services in patients so it can be give our satisfaction in patients.